Peran Political Connection dalam Memoderasi Ukuran Perusahaan dan Keberadaan Perempuan terhadap Profitabilitas Perusahaan Perbankan di Indonesia - Indra Faisal Rizki Mufid; Khalida Kumalasari (Journal of Innovative and Creativity, 2026)
This study examines the relationship between company size and the presence of women with banking profitability in Indonesia, with political connections as a moderating variable. Profitability in this study is determined by the return on assets (ROA) ratio. This study uses 42 banking companies listed on the Indonesia Stock Exchange with observations from 2020 to 2024. The research analysis was conducted using multiple regression to measure the effects of company size and the presence of women on profitability, and using moderated regression to test the moderating effect of political connections on the strength of these effects. This study shows that company size positively affects banking profitability. Meanwhile, the presence of women has no effect on banking profitability. Furthermore, the moderating effect of political connections strengthens the influence of company size and female representation on banking profitability. This study finds that Political connections in banking companies can help banks achieve profitability through company size and female representation.